Demystifying the Sacred : Blasphemy and Violence from the French Revolution to Today - Bouwers, Eveline (2022)
This book investigates the relationship between blasphemy and violence in modern history, with a focus on cases from the European world, including its (post-) colonial ties. Spanning from the late-eighteenth century to today, it shows how cultures of blasphemy, and related acts of heresy, apostasy and sacrilege, have interacted with different forms of violence, committed against both the sacred and the secular.